The Fed Response to Equity Prices and Inflation - Dupor, Bill; Conley, Timothy (American Economic Review, 2004)
A number of researchers and market observers hold that the dramatic increase during the 1990's and subsequent decline in U.S. stock prices were due to non-fundamental factors, such as irrational expectations or bubbles. If this view is correct, policymakers may be concerned with the real macroeconomic consequences of the stock market run-up. These might include overconsumption due to a perceived wealth effect or too much physical investment due to a lower financing cost of capital. Following this reasoning, the Federal Reserve could raise the Fed Funds target rate to offset perceived non-fundamental stock price increases. This policy stance may seem particularly appealing if the Fed's primary target, low and stable inflation, is already being achieved. This paper studies how Federal Reserve interestrate policy, from 1979:4 onward, responds to an aggregate measure of stock-market activity under high versus low inflation. Most existing research makes no distinction between policy across the highand low-inflation times of the past 24 years. Two conventional findings of this existing research are that the Federal Reserve: (i) raises the short-term real interest rate in response to inflation and (ii) does not change policy in response to equity price movements.1